Corpo-bureaucratizing Community Forest: Commercialization and Increased Financial Transaction in Community Forestry User Groups in Nepal - Paudel, Dinesh; Khatri, Dil Bahadur; Paudel, Govinda (Journal of Forest and Livelihood, 2013)
Based on the analysis of financial transactions and decision making procedures in Community Forest User Groups (CFUGs) in Nepal, this paper argues that community forestry is adapting techno-bureaucratic and corporate culture, replacing indigenous ways of community governance and by placing market elements into existing hierarchies and power asymmetries of local communities. It also argues that the trend of commercialization in community forestry has increased not because of the rational economic decisions made not on the basis of increased demands and surplus supply but because of a combination of economic and non-economic factors that create conditions necessary for commercialization as the next possible step in community-managed resources. In doing so this paper attempts to understand the dynamics, mechanisms and extent of CFUGs’ financial transactions through conceptualizing links of community forestry with extra-local economic forces, and also provides alternative ways of managing community resources for increased pro-poor outcomes. This study is based on in-depth analyses of national and district databases of CFUG funds, and ethnographic studies of 8 selected CFUGs from different parts of the country. DOI: http://dx.doi.org/10.3126/jfl.v9i1.8587 Journal of Forestry and Livelihood Vol.9(1) 2010 1-15